Dietary fat increases quercetin bioavailability in overweight adults. Issue 5 (15th January 2013) - Guo, Yi; Mah, Eunice; Davis, Catherine G.; Jalili, Thunder; Ferruzzi, Mario G.; Chun, Ock K.; Bruno, Richard S.
<x xml:space="preserve">Abstract</x> Scope Epidemiologic evidence supports that dietary quercetin reduces cardiovascular disease (CVD) risk, but its oral bioavailability is paradoxically low. The aim of this study was to determine whether dietary fat would improve quercetin bioavailability in adults at high risk for CVD and to assess lipid‐mediated micellarization of quercetin in vitro. Methods and results In a randomized, cross‐over study, overweight/obese men and postmenopausal women (n = 4 M/5 F; 55.9 ± 2.1 years; 30.8 ± 1.4 kg/m2) ingested 1095 mg of quercetin aglycone with a standardized breakfast that was fat‐free (<0.5 g), low‐fat (4.0 g), or high‐fat (15.4 g). Plasma was obtained at timed intervals for 24 h to measure quercetin and its methylated metabolites isorhamnetin and tamarixetin. Compared to the fat‐free trial, plasma quercetin maximum concentration (Cmax), and area under curve (AUC0–24 h) increased (p < 0.05) by 45 and 32%, respectively, during the high‐fat trial. During the high‐fat trial, isorhamnetin Cmax and AUC0–24 h also increased by 40 and 19%, respectively, whereas Cmax and AUC0–24 h of tamarixetin increased by 46 and 43%, respectively. Dietary fat dose‐dependently increased micellarization efficiency of quercetin aglycone in vitro. Conclusion Dietary fat improves quercetin bioavailability by increasing its absorption, likely by enhancing its micellarization at the small intestine.